The viability of business process reengineering : introduction of electronic billing presentment and payment (EBPP) for Telekom Malaysia Berhad - Sim, Jason Kiam Howe (Universiti Malaysia Sarawak, (UNIMAS), 2003)
The popularity of Internet nowadays has made headlines about E-Commerce and also the vast growing application of Electronic Bill Presentment and Payment (EBPP). This paper studies on the business process reengineering in implementing the EBPP for Telekom Malaysia Berhad. It identifies the critically success factors for the EBPP system and also studies the viability of the proposed EBPP system